VD_FINDINFO 117/2011/DCA vom 31. August 2011 - VD Tribunal cantonal (2011)
SOCIÉTÉ SIMPLE, CONTRAT D'OUVERTURE DE CRÉDIT, CRÉDIT DE CONSTRUCTION, COMPTE COURANT | 143 al. 1 CO, 147 al. 2 CO, 312 CO, 530 CO